Method for analysis of psychopharmaceuticals in real industrial wastewater and groundwater with suspended organic particulate matter using solid phase extraction disks extraction and ultra-high performance liquid chromatography/time-of-flight mass spectrometry - Křesinová, Zdena; Linhartová, Lucie; Petrů, Klára; Krejčová, Lucie; Šrédlová, Kamila; Lhotský, Ondřej; Kameník, Zdeněk; Cajthaml, Tomáš (Journal of chromatography. A, 2016)
A rapid and reliable analytical method was developed for the quantitative determination of psychopharmaceuticals, their precursors and by-products in real contaminated samples from a pharmaceutical company in Olomouc (Czech Republic), based on SPE disk extraction and detection by ultra performance liquid chromatography, combined with time-of-flight mass spectrometry. The target compounds were quantified in the real whole-water samples (water including suspended particles), both in the presence of suspended particulate matter (SPM) and high concentrations of other organic pollutants. A total of nine compounds were analyzed which consisted of three commonly used antidepressants (tricyclic antidepressants and antipsychotics), one antitussive agent and five by-products or precursors. At first, the SPE disk method was developed for the extraction of water samples (dissolved analytes, recovery 84-104%) and pressurised liquid extraction technique was verified for solid matrices (sludge samples, recovery 81-95%). In order to evaluate the SPE disk technique for whole water samples containing SPM, non contaminated groundwater samples were also loaded with different amounts (100 and 300mgL(-1)) of real contaminated sludge originating from the same locality. The recoveries from the whole-water samples obtained by SPE disk method ranged between 67 and 119% after the addition of the most contaminated sludge. The final method was applied to several real groundwater (whole-water) samples from the industrial area and high concentrations (up to 10(3)μgL(-1)) of the target compounds were detected. The results of this study document and indicate the feasibility of the SPE disk method for analysis of groundwater.
Keywords: Solid Phase Extraction; chemické látky znečišťující vodu; Wastewater; Water Pollutants, Chemical; monitorování životního prostředí; Sludge; podzemní voda; vysokoúčinná kapalinová chromatografie; Particulate Matter; SPE disks; odpadní voda; hmotnostní spektrometrie; Psychotropic Drugs; Chromatography, High Pressure Liquid; Whole-water; Czech Republic; Groundwater; psychotropní léky; Environmental Monitoring; Waste Water; extrakce na pevné fázi; Mass Spectrometry; Česká republika; Pharmaceuticals; Suspended particulate matter; pevné částice